Clinical and molecular phenotypes of low-penetrance variants of NLRP3: diagnostic and therapeutic challenges - Kümmerle-Deschner, Jasmin; Blank, Norbert (Arthritis & rheumatology, 2017)
Objective Cryopyrin-associated periodic syndromes (CAPS) result from gain-of-function mutations in the NLRP3 gene, which causes excessive release of interleukin-1β (IL-1β) and systemic inflammation. While pathogenetic NLRP3 variant phenotypes are well-characterized, low-penetrance NLRP3 variants represent a significant clinical challenge. The aims of this study were to determine the clinical phenotype, the in vitro biologic phenotype, and the effect of anti-IL-1 treatment in patients with low-penetrance NLRP3 variants. Methods A multicenter study of consecutive symptomatic patients with low-penetrance NLRP3 variants recruited from 7 centers between May 2012 and May 2013 was performed. The observed findings were transferred into a study database, from which they were extracted for analysis. Controls were patients with a known pathogenetic NLRP3 variant. Clinical presentation and CAPS markers of inflammation were captured. Functional assays of inflammasome activation, including caspase 1 activity, NF-κB release, cell death, and IL-1β release, were performed. Treatment effects of IL-1 were determined. Comparisons between low-penetrance and pathogenetic NLRP3 variants were performed. Results The study included 45 patients, 21 of which were female (47%); 26 of the patients (58%) were children. NLRP3 low-penetrance variants identified in the patients were Q703K (n = 19), R488K (n = 6), and V198M (n = 20). In the controls, 28 had pathogenetic NLRP3 variants. Patients with low-penetrance NLRP3 variants had significantly more fever (76%) and gastrointestinal symptoms (73%); eye disease, hearing loss, and renal involvement were less common. Functional inflammasome testing identified an intermediate phenotype in low-penetrance NLRP3 variants as compared to wild-type and pathogenetic NLRP3 variants. All treated patients responded to IL-1 inhibition, with complete response documented in 50% of patients. Conclusion Patients with low-penetrance NLRP3 variants display a distinct clinical phenotype and an intermediate biologic phenotype, including IL-1β and non-IL-1β-mediated inflammatory pathway activation.
Gesehen am 27.11.2018